Investigation of the Supply Chain Strategy Impact on the Customer Services and Supervisors - Dhevy Puswiartika; Zahrotur Rusyda Hinduan; Marina Sulastiana; Diana Harding (International Journal of Supply Chain Management, 2020)
Abstract— The study aims to identify the supply chain management and its impact on customer service, as well as indicating the role of supply chain management in improving sales and identifying the views of managers working in the corporate about supply chain management. Relying on the mindfulness framework, we argue that dispositional mindfulness has an impact on workplace outcomes, include service climate. Supply chain strategy tested as mediators of this relationship. This study was an explanatory survey among supervisors of the railway transportation service provider in Jakarta, Indonesia. The quota sampling technique was performed. The participants in this study were 357 supervisors. They filled the self-report questionnaires. The data analyzed by using Structural Equation Modelling with Lisrel 8.7 software. Results indicated that those with greater mindfulness report more positive service climate’ perception, and greater supply chain strategy. As expected, the relationship between mindfulness and service climate was mediated by supply chain strategy. The theoretical implication of this study was the empirical evidence regarding the mechanism that mediates the impact of mindfulness on workplace outcomes, with supply chain strategy as a potential mediating role. Results support the usefulness of further examination of the benefits of mindfulness in the workplace context.